2023
DOI: 10.1002/jor.25698
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transphyseal screw induces varus proximal femoral growth modulation in a growing pig model—A three‐dimensional analysis

Michael J. Kutschke,
Harry K. W. Kim

Abstract: Bone and joint angular deformities are common pediatric orthopedic problems that are often corrected surgically. Previous studies successfully demonstrated proximal femoral growth modulation in animal models, however outcome measurements were limited by two‐dimensional analysis. In this study, six Yorkshire cross male piglets were treated with unilateral percutaneous transphyseal screw placement across the medial aspect of the proximal femoral physis and analyzed using three‐dimensional (3D) techniques. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For instance, it has been shown that proximal and distal femoral derotational osteotomies may impact frontal plane alignment, resulting in varus and valgus effects, respectively [ 24 ]. Therefore, 3D post‐operative evaluation quantifying 3D ΔFR is relevant specifically when introducing novel surgical approaches [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that proximal and distal femoral derotational osteotomies may impact frontal plane alignment, resulting in varus and valgus effects, respectively [ 24 ]. Therefore, 3D post‐operative evaluation quantifying 3D ΔFR is relevant specifically when introducing novel surgical approaches [ 17 ].…”
Section: Discussionmentioning
confidence: 99%